2016
DOI: 10.1016/j.jfe.2015.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Decentralization, market integration and efficiency-equity trade-offs: Evidence from Joint Forest Management in Ethiopian villages

Abstract: Extant literature on Joint Forest Management (JFM) impact evaluation has concluded that it generally does not provide sufficient incentives to justify the costs that forest use restrictions impose on local people. However, there is a dearth of evidence concerning whether alternative JFM intervention with improved market linkages for non-timber forest products has similar implications. In this study, we evaluated the income and distributive effects of a JFM program in Ethiopia in which additional support was pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 50 publications
1
13
0
Order By: Relevance
“…For instance, individuals who support conservation may be more inclined to participate in decision-making processes and have higher expectations for what qualifies as meaningful participation. Previous studies that have implied factors such as proximity to forests and the benefits households obtain from forest resources can also influence level of participation in CFM programs (e.g., Maskey et al 2006, Gelo et al 2016. Because participation would enable individuals to shape management programs to improve their use of forest resources, it stands to reason that those with a vested interest in forests would be inclined to participate.…”
Section: Participation and Support For Forest Conservationmentioning
confidence: 99%
“…For instance, individuals who support conservation may be more inclined to participate in decision-making processes and have higher expectations for what qualifies as meaningful participation. Previous studies that have implied factors such as proximity to forests and the benefits households obtain from forest resources can also influence level of participation in CFM programs (e.g., Maskey et al 2006, Gelo et al 2016. Because participation would enable individuals to shape management programs to improve their use of forest resources, it stands to reason that those with a vested interest in forests would be inclined to participate.…”
Section: Participation and Support For Forest Conservationmentioning
confidence: 99%
“…Reports of CBFM schemes largely benefiting the rich more than the poor are very frequent in the case study countries. Gelo et al (2016) specifically stated that market linkage is fundamental to enhance CBFM's contributions to poverty alleviation, food security, and community well-being. In all the study countries, product management was observed to be one of the weakest and less explicitly stated CBFM framework attributes.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in Ethiopia, after the introduction of PFM in the Bonga forest, the mean annual household income of member households increased from ETB 1589 (Ethiopian Birr; equivalent to US$71 at current rate) to ETB 2433 (Gobeze et al 2009). A similar report from the same country showed that annual income grew by about ETB 400 (Gelo et al 2016). Community based forest managements were also proven to improve welfare (Kellert et al 2000, Gelo et al 2013).…”
Section: Community Based Forest Management and Poverty Reduction (Sdg 1)mentioning
confidence: 96%
See 2 more Smart Citations